A profile of brain reserve in adults at genetic risk of Alzheimer's disease. Issue 1 (9th June 2021) - Coughlan, Gillian; Zhukovsky, Peter; Voineskos, Aristotle; Grady, Cheryl
Abstract: Introduction: The apolipoprotein E ( APOE ) ε4 allele is the greatest genetic risk factor for Alzheimer's disease (AD). Our aim was to identify the structural brain measures that mitigate the negative effect of APOE ε4 on cognition, which would have implications for AD diagnosis and treatment trial selection. Methods: A total of 742 older adults (mean age: 70.1 ± 8.7 years) were stratified by APOE status and classified as cognitively normal (CDR 0) or with very mild dementia (CDR 0.5). Regional brain volume and cognitive performance were measured. Results: There were significant interactions between APOE and CDR on the left precuneus and on bilateral superior frontal volumes. These regions were preserved in CDR‐0 ε3/ε4 and ε4/ε4 carriers but were reduced in CDR‐0.5 ε3/ε4 and ε4/ε4 carriers, compared to their respective ε3/ε3 counterparts. Educational attainment predicted greater brain reserve. Discussion: This pattern of preserved brain structure in cognitively normal ε4 carriers with comprised medial temporal volume is consistent with the theory of brain reserve.